2013
DOI: 10.1097/01.jto.0000437419.31348.a4
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome after En Bloc Resection of Non–Small-Cell Lung Cancer Invading the Pulmonary Sulcus and Spine

Abstract: En bloc resection of the lung, chest wall, and spine for non-small-cell lung cancer invading the pulmonary sulcus and spine is feasible in experienced centers with excellent long-term outcome after careful patient selection. Response to induction was an independent significant prognostic factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 21 publications
(43 reference statements)
3
40
1
Order By: Relevance
“…Subsequently, several modifications of this technique were reported (26)(27)(28). Radical surgery with acceptable local tumor control became a real possibility thanks to new surgical techniques such as laminectomy, partial or hemivertebrectomy, complete resection of vertebral body, and vascular by-pass, as well as the common practice of working in a multidisciplinary team (thoracic surgeon, neurosurgeon, orthopedic surgeon, vascular surgeon) (24,(29)(30)(31)(32)(33). During the 1990s, the increasing experience with combined modality therapy suggested that induction chemo-radiotherapy followed by resection could become an effective treatment strategy for stage III NSCLC (34).…”
Section: A B Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, several modifications of this technique were reported (26)(27)(28). Radical surgery with acceptable local tumor control became a real possibility thanks to new surgical techniques such as laminectomy, partial or hemivertebrectomy, complete resection of vertebral body, and vascular by-pass, as well as the common practice of working in a multidisciplinary team (thoracic surgeon, neurosurgeon, orthopedic surgeon, vascular surgeon) (24,(29)(30)(31)(32)(33). During the 1990s, the increasing experience with combined modality therapy suggested that induction chemo-radiotherapy followed by resection could become an effective treatment strategy for stage III NSCLC (34).…”
Section: A B Cmentioning
confidence: 99%
“…This limitation was caused by the lack of proper surgical techniques to achieve a radical resection and no multimodality treatment. At present, surgical procedures such as laminectomy, partial or hemivertebrectomy or complete resection of vertebral body can be performed in the context of a triple modality therapy, with high rates of complete surgical resection, good long-term survival, and acceptable morbidity and mortality (24,32,33,56,57) (Figure 7). The careful selection of patients and of specialized centers with interdisciplinary teams of thoracic and spine surgeons is indispensable.…”
Section: Limits To Resectabilitymentioning
confidence: 99%
“…77 Although the findings from the Canadian study group suggested, in previous reports, that complete or near-complete pathologic response to induction chemoradiation therapy was associated with a significantly longer survival, the pooled data analysis (which included data from the Canadian study group) did not find a significant effect on survival due to downstaging via induction therapy. 77,80 It is possible that the finding from the Canadian study group was spurious. It is, however, also possible that such an effect truly exists but that its signal was lost in the heterogeneity of the multiple treatment approaches in the pooled analysis.…”
Section: Pulmonary Sulcus Tumours With Spine Invasionmentioning
confidence: 80%
“…In the end, the only inference that can be currently made is that induction therapy does not appear to result in worse outcomes and may possibly result in better outcomes by inducing complete or nearcomplete pathologic response. 77,80 In conclusion, although we do not have and are unlikely to get Level I evidence in this low-incidence and complex disease, our current best evidence suggests that T4 NSCLC invading the spine is potentially resectable and curable. The best outcomes appear to be with en-bloc resection and the only significant predictor of survival appears to be achievement of an R0 resection.…”
Section: Pulmonary Sulcus Tumours With Spine Invasionmentioning
confidence: 99%
“…According to many authors, prognosis in patients diagnosed with the Pancoast tumour depends mainly on T stage of tumour, response to preoperative chemo-radiotherapy and completeness of resection [1][2][3][4][5][6]. The surgical treatment itself is associated with 5 % mortality and 7-38 % mortality rates [4].…”
Section: Introductionmentioning
confidence: 99%